Conselho Participativo Municipal de São Paulo: utopia viável em uma sociedade distópica - Santos, Antônia Conceição dos (2022)
The present study consists of a procedural historical analysis of the Municipal Participative Council of São Paulo (CMP), during the administration of Mayor Fernando Haddad (2013 - 2016), aiming to understand the practice and council dynamics in the 2014-2016 years, in the 32 Regional Subprefectures of São Paulo. The objective of this thesis is to contribute to the understanding of the possible contradictions between institutionalized social participation within the Municipal Participative Council in its implementation process and the concepts around theories about participative democracy, the social and ideopolitical factors that engendered its constitution. Through a set of basic assumptions contained in the theoretical constructions related to the theme of participative democracy; empirically explore convergences and contradictions between theoretical assumptions related to participative democracy and inferences found within the scope of the Municipal Participative Council of the city of São Paulo. The theme refers to the model of Participative and Representative Democracy, deserving special attention to the Municipal Participative Council of the city of São Paulo. Dealing with this topic is also discussing issues directly related to political participation, an elementary phenomenon to the idea of participative democracy, with a view to understanding how Brazilian society and the country's political institutions have developted to the point where representative democracy coexists with typically participative instruments. The research seeks not only to understand the contradictions and tensions in the daily practice of the Council in question, but also to contribute to the democratic improvement of social control in the territorial scope